THE CONSTRUCTIVE RELATIONSHIP BETWEEN ACCOUNTING AND PERFORMANCE IN THE CONTEXT OF CORPORATE GOVERNANCE AND ACCOUNTING NORMALIZATION - Mihai SAVIN (Challenges of the Knowledge Society)
Since the emergence of the concept of corporate governance, there was a close connection between this concept and accounting, which is enforced by the fact that the latter must reflect, in a conventional manner, all the economic facts that affect the economic entity, meaning the facts related to the production, distribution and consumption of wealth, but also to the creation of value for shareholders and other stakeholders, in this sense being the most reliable, efficient and effective method of economic observation. The explanations provided by the economic science according to which an economic entity is considered an individual agent who seeks to maximize profits no longer constitute a support for explaining the continental, renan or Anglo-Saxon accounting model, and as such the scientific basis of accounting must be seeked in the scientific approach of the concept of corporate governance, which has as overall objective the study of the manner to lead, to steer, to structure, to develop, to control an entity (company, public institution etc.), to create value for shareholders and other interest groups. Corporate governance and also the normalization of the accounting have managed for the first time to provide a complete and consistent representation of the economic entity, meaning they defined the essential tools to manage and control the economic activity, to measure its overall performance.